Solid state physics - Camley, Robert (Academic, 2011)
Solid state physics is the branch of physics primarily devoted to the study of matter in its solid phase, especially at the atomic level. This prestigious serial presents timely and state-of-the-art reviews pertaining to all aspects of solid state physics.